Human rights between the carpet newspaper and the international law - Ahmed Abel Al-Rakabi, .Dr. Taiseer (Basra studies journal, 2022)
The subject of human rights takes priority in the world’s thought and approach and in the application of the most important ways to lead a person to a dignified life, and since these rights are the focus of the human world’s thought in various religions and races, the research attracted me to study (Human Rights in the Sajadiya newspaper of Imam Zain al-Abidin and its comparison with the Universal Declaration of Human Rights) in which I dealt with A comparative study between the legal law represented by (Al-Sahifa Al-Sajjadia) and the positive law represented by (the Universal Declaration). Human rights are rights inherent to all human beings, whatever their nationality, place of residence, gender, national or ethnic origin, colour, religion, language or any other status. We all have the right to equal access to our human rights without discrimination.